Statistical Phrase-based Machine Translation: Experiments with Brazilian Portuguese - Aziz, Wilker F.; Pardo, Thiago A. S.; Paraboni, Ivandré (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2009: Anais do VII Encontro Nacional de Inteligência Artificial, 2009)
Statistical approaches have recently emerged as the main paradigm in Machine Translation (MT) research. In previous work we have shown that results of a simple statistical word-based MT system may be highly comparable to those produced by a rule-based approach for closely-related languages such as Brazilian Portuguese and European Spanish. In this work we take the discussion one step further and present evidence that a more sophisticated (namely, phrase-based) translation model may outperform rule-based translation for this language pair, and additional results of a first experiment in Portuguese/English phrase-based statistical MT.